No effect of partial-body cryotherapy on restoration of countermovement jump or well-being performance in elite rugby union players during the competitive phase of the season - Grainger, A.; Comfort, P.; Heffernan, S. (International Journal of Sports Physiology and Performance, 2020)
Purpose: Partial body cryotherapy (PBC) has been shown to be beneficial for postexercise recovery; however, no study has demonstrated the effectiveness of PBC for recovery following elite rugby union training. Rugby union is a unique sport that involves high-velocity collisions and may induce greater performance decrements than other sports; thus, PBC could be beneficial. The application of PBC in "real world" has rarely been investigated during the competitive phase of a playing season and warranted investigation. Methods: In a counterbalanced sequential research design, professional rugby athletes (n=18; age 25.4 [4.0] y; training age 7.2 [4.0] y; mass 99.8 [10.6] kg; height 188.3 [6.0] cm) were assigned to a 12-week PBC intervention, washout period (4 wk), and reassessed as their own controls. Self-reported well-being, muscle soreness, sleep quality, and countermovement jump height were assessed before and 40 hours after "real-world" training. Wilcoxon signed-rank tests and Cohen d were used for statistical analysis. Results: No differences were observed between PBC and control conditions (P>.05; d=0.00-0.14) for well-being (-0.02% [0.08%] vs 0.01% [0.06%]), muscle soreness (-0.01% [0.11%] vs 0.01% [0.16%]), sleep quality (-0.03% [0.14%] vs 0.10% [0.29%]), or countermovement jump height (36.48-36.59 vs 38.13-37.52 cm; P=.54). Conclusions: These results suggest PBC is ineffective for the restoration of selected performance parameters during the performance maintenance phase of the competitive season. To ascertain the appropriation of its use, future investigations should seek to assess the use of cryotherapies at various phases of the elite rugby union competitive season.